Last girl ghosted - Unger, Lisa, 1970- (Toronto, Ontario, Canada : Park Row Books, 2021)
Believing she had found true love on a dating app, a young woman is shocked when her lover intentionally disappears and she discovers many other girls who also thought they were in love with the same man
She met him through a dating app; what she thought might be just a quick hookup quickly became much more. She fell for him, hard. Then, just as things were getting real, he stood her up. Then he disappeared: profiles deleted, phone disconnected. She was ghosted. Soon she learns there were others. Girls who thought they were in love... girls who later went missing. She had been looking for a connection, but now she is looking for answers. She finds herself on a dangerous hunt... and she's not sure whether she's the predator or the prey. -- adapted from jacket
Keywords: Advice columnists -- Fiction; Online dating -- Fiction; Dating (Social customs) -- Fiction; Secrecy -- Fiction; Missing persons -- Fiction; New York (N.Y.) -- Fiction; Psychological fiction; Suspense fiction; Novels; Psychological fiction; Thrillers (Fiction)